Treatment strategies for intrauterine adhesion: focus on the exosomes and hydrogels - Wu, Fengling; Lei, Ningjing; Yang, Shenyu; Zhou, Junying; Chen, Mengyu; Chen, Cheng; Qiu, Luojie; Guo, Ruixia; Li, Yong; Chang, Lei (Frontiers in Bioengineering and Biotechnology, 2023)
Intrauterine adhesion (IUA), also referred to as Asherman Syndrome (AS), results from uterine trauma in both pregnant and nonpregnant women. The IUA damages the endometrial bottom layer, causing partial or complete occlusion of the uterine cavity. This leads to irregular menstruation, infertility, or repeated abortions. Transcervical adhesion electroreception (TCRA) is frequently used to treat IUA, which greatly lowers the prevalence of adhesions and increases pregnancy rates. Although surgery aims to disentangle the adhesive tissue, it can exacerbate the development of IUA when the degree of adhesion is severer. Therefore, it is critical to develop innovative therapeutic approaches for the prevention of IUA. Endometrial fibrosis is the essence of IUA, and studies have found that the use of different types of mesenchymal stem cells (MSCs) can reduce the risk of endometrial fibrosis and increase the possibility of pregnancy.Recent research has suggested that exosomes derived from MSCs can overcome the limitations of MSCs, such as immunogenicity and tumorigenicity risks, thereby providing new directions for IUA treatment. Moreover, the hydrogel drug delivery system can significantly ameliorate the recurrence rate of adhesions and the intrauterine pregnancy rate of patients, and its potential mechanism in the treatment of IUA has also been studied. It has been shown that the combination of two or more therapeutic schemes has broader application prospects; therefore, this article reviews the pathophysiology of IUA and current treatment strategies, focusing on exosomes combined with hydrogels in the treatment of IUA. Although the use of exosomes and hydrogels has certain challenges in treating IUA, they still provide new promising directions in this field.